In Vitro and In Vivo Effect of pH-Sensitive PLGA-TPGS-Based Hybrid Nanoparticles Loaded with Doxorubicin for Breast Cancer Therapy - Renata S. Fernandes; Raquel Gregório Arribada; Juliana O. Silva; Armando Silva-Cunha; Danyelle M. Townsend; Lucas A. M. Ferreira; André L. B. Barros (MDPI AG, 2022)
Doxorubicin (DOX) is an antineoplastic agent clinically employed for treating breast cancer patients. Despite its effectiveness, its inherent adverse toxic side effects often limit its clinical application. To overcome these drawbacks, lipid-polymer hybrid nanoparticles (LPNP) arise as promising nanoplatforms that combine the advantages of both liposomes and polymeric nanoparticles into a single delivery system. Alpha-tocopherol succinate (TS) is a derivative of vitamin E that shows potent anticancer mechanisms, and it is an interesting approach as adjuvant. In this study, we designed a pH-sensitive PLGA-polymer-core/TPGS-lipid-shell hybrid nanoparticle, loaded with DOX and TS (LPNP_TS-DOX). Nanoparticles were physicochemically and morphologically characterized. Cytotoxicity studies, migration assay, and cellular uptake were performed in 4T1, MCF-7, and MDA-MB-231 cell lines. Antitumor activity in vivo was evaluated in 4T1 breast tumor-bearing mice. In vitro studies showed a significant reduction in cell viability, cell migration, and an increase in cellular uptake for the 4T1 cell line compared to free DOX. In vivo antitumor activity showed that LPNP-TS-DOX was more effective in controlling tumor growth than other treatments. The high cellular internalization and the pH-triggered payload release of DOX lead to the increased accumulation of the drugs in the tumor area, along with the synergic combination with TS, culminating in greater antitumor efficacy. These data support LPNP-TS-DOX as a promising drug delivery system for breast cancer treatment.